(untitled) (INNOVATIVE ECONOMY, 2024)
Chernyshova T.V. OPEN INNOVATION AS A COMPLEX MECHANISM OF MODERN INNOVATIVE DEVELOPMENT Purpose. The aim of the article is to study the regularities of open innovations in the process of modern innovative development and development of a complex model that explains the cause-and-effect mechanism of the development of open innovations in the multiplicity of their manifestation. Methodology of research. The following research methods were applied to achieve the goal: to identify the essence of the concept of “open innovation” – methods of analysis and synthesis; for the accumulation of disjointed, but causally connected facts, concepts – methods of induction and deduction in their dialectics; for the formulation of theoretical generalizations – the abstract and logical method; for visualization of research results – graphic method; for the definition and classification of approaches to the interpretation of the studied category – the method of systematization. Findings. The essence of the concept of "open innovation" was investigated. The available interpretations of “open innovations” in the economic literature are summarized and the key markers of the analysed concept are identified. The classification of the principles of open innovation was further developed. A matrix of comparison of the properties of related methods of the openness paradigm in the innovation process was obtained. A dynamic system model of the open innovation development mechanism was developed. Originality. The theoretical aspects of innovative development in the open innovation paradigm, which characterize the development of the principle of openness in a variety of related methods, have gained further development. Practical value. The results of the conducted research can be applied to ensure further systematic research of the modern innovation process in the paradigm of open innovation and the formation of effective programs and tools to ensure their development in Ukraine. Key words: open strategy, open innovation process, open innovation, innovative development, crowdsourcing, co-creation, socially responsible marketing.